Pengabdian Masyarakat dalam Mendukung Program Pemerintah melalui Posyandu ILP di Puskesmas Bontang Selatan I: Pengabdian - Erni Ameliya; Dinda Salmi Nabiya; Ashri Rahmaya Nur; Ega Januaryl Pratama Putri; Octa Ida Manullang; Ratih Wirapuspita Wisnuwardani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Public Health Centers (Puskesmas) as primary healthcare facilities play a crucial role in promotive and preventive efforts against non-communicable diseases (NCDs), including hypertension, diabetes mellitus, and high cholesterol. The Integrated Primary Services Program (ILP) implemented at Bontang Selatan I Health Center aims to raise community awareness of the importance of regular health check-ups. This initiative involves posyandu cadres, healthcare workers, and university students in conducting screenings for blood pressure, blood glucose, and cholesterol levels at two community health posts: Berseri 1 and Kasih Ibu 2. The results indicate a higher prevalence of hypertension, hyperglycemia, and hypercholesterolemia among the elderly at Berseri 1, likely due to poor dietary habits rich in sugar, salt, and fat. In contrast, more stable health profiles were observed at Kasih Ibu 2, which had a predominance of younger, more health-conscious participants. Direct health education following the screenings proved effective in increasing awareness of NCD risks. This program aligns with government efforts to control NCDs through community-based approaches at Puskesmas and Posyandu. Strengthening health education, routine monitoring, and cadre training is essential to improve the program's effectiveness